OSTEOSARCOMA HAS NOT BECOME ATTENTION TO SOCIETY PROFILE OF OSTEOSARCOMA PATIENTS AT DR. SOETOMO GENERAL HOSPITAL SURABAYA "A RETROSPECTIVE STUDY” - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Yunus Abdul Bari; Yesa Suwandani (Journal Orthopaedi and Traumatology Surabaya)
Background: Osteosarcoma is the most common bone neoplasm found in the community but evaluation osteosarcoma cases in RSUD Dr. Soetomo has not been updated since 1995.